UPPER MANTLE STRUCTURE OF EASTERN ASIA FROM MULTIMODE SURFACE WAVEFORM TOMOGRAPHY - Priestley K.; McKenzie D.; Pilidou S.; Debayle E. (My University, 2006)
We present a new three-dimensional Sv wave speed and azimuthal anisotropy model for the upper mantle of eastern Asia constrained by the analysis of more than 17,000 vertical component multimode Rayleigh wave seismograms. This data set allows us to build an upper mantle model for Asia with a horizontal resolution of a few hundred kilometers extending to ~400 km depth. At 75-100 km depth, there is approximately ±9% wave speed perturbation from the "smoothed PREM" reference model used in our analysis, and the pattern of azimuthal anisotropy is complex. Both the amplitude of the Sv wave speed heterogeneity and the complexity and amplitude of the azimuthal anisotropy decrease with depth. Above ~200 km depth the upper mantle structure of the model correlates with surface geology and tectonics; below ~200 km depth the structures primarily reflect the advection of material in the upper mantle. Since shear wave speed is principally controlled by temperature rather than by composition, Vs(z) can be used to calculate the temperature T(z), and hence map the lithospheric thickness. We use the relationship of Priestley and McKenzie to produce a contour map of the lithospheric thickness of eastern Asia from the surface wave tomography. This shows an extensive region of thick lithosphere beneath the Siberian Platform and the West Siberian Basin that extends to the European Platform, forming the stable Eurasian craton or core. The eastern portion of the Eurasian craton has controlled the geometry of continental deformation and the distribution of kimberlites in eastern Asia. Copyright 2006 by the American Geophysical Union.